Improvement Of Traffic Capacity For Stadium Intersection In Al-Samawah City - I. Ahmed, Ahmed; F. Jasim, Abbas (Iraqi Journal of Civil Engineering, 2013)
Capacity and level of service are the control points of the analysis of intersections and must be fully considered to evaluate the overall operator of the intersection. The objectives of the present study include the analysis, evaluation and improvement of the operation for Stadium Intersection in Samawah city and to present the best proposal to enhance the performance from the capacity point of view. To achieve these objectives, the estimated distribution of the traffic data in different directions that required for the traffic and geometrical analysis were gathered manually, while HCS traffic program is used for the requirements of traffic analysis process. It has been concluded that the flyover between Al-Zwaid Street – Stadium Street (Proposal No.5) is the best proposal to improve the operation ability of Stadium Intersection.